2010
DOI: 10.1242/dev.050526
|View full text |Cite
|
Sign up to set email alerts
|

The miR-143-adducin3 pathway is essential for cardiac chamber morphogenesis

Abstract: SUMMARYDiscovering the genetic and cellular mechanisms that drive cardiac morphogenesis remains a fundamental goal, as threedimensional architecture greatly impacts functional capacity. During development, accurately contoured chambers balloon from a primitive tube in a process characterized by regional changes in myocardial cell size and shape. How these localized changes are achieved remains elusive. Here, we show in zebrafish that microRNA-143 (miR-143) is required for chamber morphogenesis through direct r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 53 publications
(93 reference statements)
3
67
0
1
Order By: Relevance
“…The ejection fraction (EF) of the ventricle was 2272% at 48 hpf, comparable to a previous report (Deacon et al, 2010) and then 21.5 71.6%, 21.7 71.5%, 2372%, respectively at 72, 96 and 120 hpf ( Fig. 4) .…”
Section: Functional Changes Of the Ventricle During Developmentsupporting
confidence: 90%
“…The ejection fraction (EF) of the ventricle was 2272% at 48 hpf, comparable to a previous report (Deacon et al, 2010) and then 21.5 71.6%, 21.7 71.5%, 2372%, respectively at 72, 96 and 120 hpf ( Fig. 4) .…”
Section: Functional Changes Of the Ventricle During Developmentsupporting
confidence: 90%
“…miR-143 is one of the most enriched miRs during embryonic development, with an essential role for myocardial proliferation, cardiac function and cardiogenesis. 28 Besides, miR-143 also showed reversed expression in some carcinomas and regenerative from Dr. Xu Meifeng (University of Cincinnati) and Dr. Ge Ruowen (National University of Singapore). The vectors were individually propagated in HEK-293 cells cultured in DMEM supplemented with 10% fetal bovine serum (FBS).…”
Section: Discussionmentioning
confidence: 98%
“…For instance, RA that is synthesized by raldh2 and diffused out from the endocardium could have a non-cell autonomous effect to the myocardium. Recently, it has been shown that miR-143 regulates adducin3 (add3), which encodes an F-actin capping protein (Deacon et al, 2010). This pathway also contributes to the correct formation of the ventricular architectures, suggesting that multiple cascades regulate chamber formation of the heart through the heartbeat-dependent expression of miR-143.…”
Section: Discussionmentioning
confidence: 99%